Adsorption-based synthesis of Co3O4/C composite anode for high performance lithium-ion batteries. (15th April 2017) - Wang, Shaofeng; Zhu, Yanping; Xu, Xiaomin; Sunarso, Jaka; Shao, Zongping
Abstract: Enhancing anode performance in lithium-ion battery is one of the key directions to enable its efficiency as energy storage device. Conversion reaction provides an attractive strategy for such enhancement where reversible reaction between transition metal oxide and lithium ion enables very high capacity attainment. This work showed that homogeneous dispersion of nanoparticle Co3 O4 within carbon network can be obtained via a facile adsorption strategy using macroporous acrylic type cation-exchange resin and heat treatments. Co3 O4 was formed in situ carbon matrix utilizing cobalt acetate as cobalt ion precursor and catalyst for carbon graphitization. The lithium half-cell utilizing such anode demonstrated the highest capacity of 928 mAh g −1 at a current rate of 200 mA g −1 and excellent rate capability, i.e., it retained 630 mAh g −1 capacity at a current rate of 1600 mA g −1 and 470 mAh g −1 capacity at a current rate of 3200 mA g −1 . The composite demonstrated higher performance than its individual constituents which highlights the synergy effect upon combining Co3 O4 and carbon. In optimizing the performance, carbon to Co3 O4 ratio becomes an important variable. To obtain maximum capacity, we showed that CO2 introduction during heat treatment can be utilized to reduce excess carbon content in such composite. Highlights: Co3 O4 /C composite is obtained via a facile adsorption strategy. The influence of Co3 O4 : C ratio on battery performance is investigated. Co3 O4 /C composite shows enhanced performances as anode in Li-ion batteries.